Analisis kendala pembelajaran daring bagi siswa madrasah ibtidaiyah - Masruro, Fufa (Patria Educational Journal (PEJ), 2024)
Tujuan penelitian untuk mendeskripsikan kendala pembelajaran daring bagi siswa sekolah dasar di MI Alhayatul Islamiyah. Sebagaimana pembelajaran tatap muka yang memiliki beberapa kelemahan, pembelajaran daring juga dimungkinkan menimbulkan kendala bagi siswa sekolah dasar. Sesuai dengan tujuannya, jenis penelitian ini yaitu deskriptif kualitatif. Teknik pengumpulan data dilakukan menggunakan observasi, wawancara, dan dokumentasi. Pedoman analisis data menggunakan teknik analisis Miles dan Huberman. Penelitian ini menunjukkan hasil bahwa pembelajaran daring menimbulkan kesulitan bagi siswa dalam beberapa hal, antara lain: (1) kesulitan dalam mengoperasikan handphone kesulitan dalam mengoperasikan handphone; (2) kesulitan dalam menyelesaikan tugas dari guru; (3) kesulitan dalam mengoperasikan handphone; dan (4) faktor lain yang disebabkan oleh lingkungan dan sarana prasarana yang kurang mendukung. Constraint analysis of online learning for madrasah ibtidaiyah students Abstract: This study aims to describe the obstacles faced by elementary school students in online learning. Such as deficiencies in face-to-face learning, online learning may also have obstacles for elementary school students. According to research objectives, this type of research is qualitative descriptive research. Data collecting by interviewing, observing, and documenting techniques. Data analysis used Miles and Huberman techniques. The result of this research indicated there are students difficulties in online learning: 1) difficulty in operating handphone; 2) difficulty in completing the tasks; 3) difficulty in understanding the material; and 4) other difficulties caused by unfavorable and unsupportive fasilities.This study aims to describe the obstacles faced by elementary school students in online learning. Such as deficiencies in face-to-face learning, online learning may also have obstacles for elementary school students. According to research objectives, this type of research is qualitative descriptive research. Data collecting by interviewing, observing, and documenting techniques. Data analysis used Miles and Huberman techniques. The result of this research indicated there are students difficulties in online learning: 1) difficulty in operating handphone; 2) difficulty in completing the tasks; 3) difficulty in understanding the material; and 4) other difficulties caused by unfavorable and unsupportive fasilities.